2011
DOI: 10.1097/aln.0b013e318212515b
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Transient Receptor Potential Vanilloid 1 Can Affect Survival, Bacterial Clearance, and Cytokine Gene Expression during Murine Sepsis

Abstract: Background Previous studies suggest that the transient receptor potential vanilloid-1 (TRPV1) has a role in sepsis but it is unclear whether its effect on survival and immune response is beneficial or harmful. Methods We studied the effects of genetic (Trpv1-knock out vs. wild-type mice) and pharmacologic disruption of TRPV1 with resiniferatoxin (an agonist) or capsazepine (an antagonist) on mortality, bacterial clearance, and cytokine expression during lipopolysaccharide or cecal ligation and puncture (CLP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
5
33
0
Order By: Relevance
“…However, we cannot overrule a role for TRPV1 in changes in the presence of bacteria in the lung at later time points. Indeed, in support of our findings, it was recently demonstrated that blood samples obtained from CLP TRPV1KO exhibited a higher bacterial load 24 h after sepsis induction that was associated with higher mortality when compared with WT mice (51).…”
Section: Discussionsupporting
confidence: 76%
“…However, we cannot overrule a role for TRPV1 in changes in the presence of bacteria in the lung at later time points. Indeed, in support of our findings, it was recently demonstrated that blood samples obtained from CLP TRPV1KO exhibited a higher bacterial load 24 h after sepsis induction that was associated with higher mortality when compared with WT mice (51).…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with the cumulative evidence that points to a protective role for TRPV1 in murine sepsis models, we observe that TRPV1 activation displays a protective phenotype of reduced proinflammation, increased anti-inflammation, and downregulation of PAI-1 in toxicity and infection models of sepsis (17,27,39,40). However, in contrast to other reports on TRPV1 in sepsis, we did not detect differences in the cytokine responses of Trpv1 2/2 and WT mice treated with LPS or Pam3Cys in the absence of NADA.…”
Section: Discussionsupporting
confidence: 64%
“…The majority of the in vivo work on NADA has focused on its neurologic and behavioral effects, and NADA's effects on inflammation have not been characterized (2,(35)(36)(37)(38). Although there are mixed studies suggesting that TRPV1 activation affects inflammation in models of sepsis, to our knowledge, no prior study has investigated in vivo the role of NADA or the NADA-TRPV1 axis in sepsis (17,27,39,40). Therefore, we tested the hypothesis that the administration of NADA would reduce acute systemic inflammation in sepsis via activation of TRPV1.…”
Section: T He Endogenous Lipid N-arachidonoyl Dopamine (Nada)mentioning
confidence: 99%
“…Interestingly, inflammatory bowel disease is associated with up‐regulation of TRPV1 in nerve fibers of the colon . Previous animal study showed that TRPV1 is involved in bacterial clearance and cytokine secretion …”
Section: Introductionmentioning
confidence: 99%